2018
DOI: 10.1590/s2175-97902018000317552
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinical and lifestyle predictors for severity of erectile dysfunction and biomarkers level in Malaysian patients

Abstract: The incidence of erectile dysfunction (ED) is rising worldwide and its prevalence is one of the main health concerns that affect overall men well-being in Malaysia. The cluster of demographic, clinical and lifestyle factors may have contributed to the severity of ED and changes in biomarkers level; nevertheless these have not been studied extensively. This cross sectional study involved a total of 276 patients with 138 was diagnosed with ED. The demographic, clinical, lifestyle factors and severity of ED were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(88 reference statements)
1
1
0
Order By: Relevance
“…This is in line with a study conducted in Ghana [35]. Similarly, another study showed that physical activity is a significant predictor of erectile dysfunction [36]. This could be due to exercise is a key aspect of a healthy lifestyle that might benefit DM patients to prevent high blood glucose levels and DM-related complications.…”
Section: Discussionsupporting
confidence: 87%
“…This is in line with a study conducted in Ghana [35]. Similarly, another study showed that physical activity is a significant predictor of erectile dysfunction [36]. This could be due to exercise is a key aspect of a healthy lifestyle that might benefit DM patients to prevent high blood glucose levels and DM-related complications.…”
Section: Discussionsupporting
confidence: 87%
“…23 However, other Malaysian studies stated that no significant association regarding household income with erectile dysfunction. 6,7,24 The limitation fo this study was that the data was obtained by self-reporting, which might have lead to recall bias. Also, there might be reporting bias from responders about ED, where gender issues are not openly acknowledged.…”
Section: Discussionmentioning
confidence: 99%